Refleksi Kebudayaan Senjata Api Kolonial dalam Perkumpulan Menembak di Pulau Jawa, 1867-1942 - Krisnaldi Putra Kurnia; Mumuh Muhsin Zakaria; Dade Mahzuni (Universitas Hamzanwadi, 2025)
This research examines firearms culture in Java during the colonial period by examining various shooting associations that were established during that period. Since 1867, various founding and activities of such associations were documented in colonial newspapers and magazines. In conjunction with that, this study aims to reconstruct the development of shooting societies in Java from their earliest mention in the newspaper in 1867 until the Japanese conquest of the Dutch East Indies. The research method used in this study is the historical method, which consists of heuristics, criticism, interpretation, and historiography. Primary sources, which include newspapers, magazines, and the Staatsblad, as well as secondary sources, such as journal articles and books relevant to this topic, were obtained through searches on the Delpher website and Google Books. Through the historical reconstruction process, this study found that the emergence of shooting societies in Java during the second half of the 19th century was inseparable from the positive perception of the Dutch towards firearms that preceded them. This positive view on firearms urged Dutch gun owners in Java to form shooting associations whose membership also extends to the natives. These associations provided their members with shooting education and entertainment through regular shooting competitions. Furthermore, these shooting associations were prone to experiencing an organisational crisis when the colonial economy experienced setbacks. The shooting associations in Java indicates that firearms had a significance in the social life of the Dutch East Indies society. Lastly, this research hopes to enrich the Indonesian historiography on topic that has yet to received widespread attention.